O UNICEF e a política de educação infantil no governo Lula - Fullgraf, Jodete Bayer Gomes (2007)
The thesis examines how the internacional agency UNICEF influences Brazilian early childhood education policies. It is based on the theoretical perspective of the globally structured agenda for education, as defined by Roger Dale. It focuses the educational policies adopted in the federal level during Luiz Inácio Lula da Silva`s first government (2002-2006). The research tries to find out in what measure the elaboration and implementation of the program Strengthened Brazilian Family of UNICEF/MEC can be interpreted as constituting a translation for the Brazilian context of transnational dynamics and processes. The empirical data included official documents obtained both in the country and abroad and interviews with professionals from the Brazilian government and UNICEF. The data collection was accomplished during the years of 2005 and 2006. These sources (interviews and documents) were analyzed in such a way as to identify relationships, convergences and conflicts that characterizes Brazilian early childhood education. The thesis demonstrates the existence of complex relationships between formulation and implementation of educational policies. The analysis sustains that UNICEF guidance influences early childhood education policies and, in doing so, weakens the guidelines defined in the Brazilian main legislation. The research reveals how the agency has been developing a simultaneous relationship of legitimation and mandate with the Brazilian state. The analysis also evidences that relationships between the Brazilian government and the international organizations doesn't happen in an unilateral way, since those influences are subject the redefinition and reinterpretations. This confirms that there is always a dialectic relationship between the global and the local level of decision